Towards a macroscope: Leveraging technology to transform the breadth, scale and resolution of macroecological data - Maria Dornelas; Elizabeth M. P. Madin; Michael Bunce; Joseph D. DiBattista; Mark Johnson; Joshua S. Madin; Anne E. Magurran; Brian J. McGill; Nathalie Pettorelli; Oscar Pizarro; Stefan B. Williams; Marten Winter; et al. (Global Ecology and Biogeography, 2019)
The problem Earth‐based observations of the biosphere are spatially biased in ways that can limit our ability to detect macroecological patterns and changes in biodiversity. To resolve this problem, we need to supplement the ad hoc data currently collected with planned biodiversity monitoring, in order to approximate global stratified random sampling of the planet. We call this all‐encompassing observational system ‘the macroscope’. The solution With a focus on the marine realm, we identify seven main biosphere observation tools that compose the macroscope: satellites, drones, camera traps, passive acoustic samplers, biologgers, environmental DNA and human observations. By deploying a nested array of these tools that fills current gaps in monitoring, we can achieve a macroscope fit for purpose and turn these existing powerful tools into more than the sum of their parts. An appeal Building a macroscope requires commitment from many fields, together with coordinated actions to attract the level of funding required for such a venture. We call on macroecologists to become advocates for the macroscope and to engage with existing global observation networks.